Pandemic and Linguistic Contamination in News Reporting: Social and Communicative Aspects - Michele Russo (Testo & Senso, 2022)
The spread of Coronavirus has contaminated people’s vocabulary. The first part of my work aims to analyse the new expressions used in British news reporting. The discussion will thereafter center on the employment of neologisms and new phrases in less formal contexts. I will accordingly dwell on the relationship between the formal and informal registers of the Coronavirus-related vocabulary by taking into account Foucault’s (1972: 96-105) theory of repeatable materiality, and Johnstone’s (2008: 133-34) theory of indexicality. Finally, I will look into some Coronavirus-related medical lexicon (Thorne 2020).